Frank Miller and the Decision to Prosecute - Frank J. Remington; Wayne A. Logan (Washington University Law Quarterly, 1991)
Frank Miller's book, Prosecution, provides many examples of how careful observation of existing prosecutorial practices can furnish a basis for reconsidering the propriety of existing legal doctrine and day-to-day practice. Unfortunately, the limited space available here precludes any such exhaustive catalog. Nevertheless, three issues raised by Miller's research merit particular attention. The first concerns the use of post-arrest warrants. Miller's painstaking description of prosecution practices in Wisconsin disclosed that the routine issuance of post-arrest warrants, a time-consuming practice, served no identifiable function. A second, and more controversial discovery centered on the respective roles of the executive and judiciary in the decision to charge a suspect with a crime. Miller discovered that although prosecutors routinely made autonomous charging decisions, existing legal doctrine made it impossible to determine whether the decision was, in theory, an executive decision for the prosecutor or a judicial decision for the trial judge. A third issue concerns the function of the post-arrest complaint, the need for which, Miller's work demonstrated, is as unclear as the need for the post-arrest warrant. This tribute will focus on Wisconsin practices, in particular as they relate to the three issues discussed above. This focus on Wisconsin, however, does not limit the utility of the analysis. Indeed, one reason for the enduring quality of the ABF survey in general was its universality; the justice systems of the field sites chosen shared fundamental administrative practices with states throughout the nation. Moreover, as will be seen, the same issues described in detail by Miller over twenty years ago still arise today throughout the country.
Keywords: Prosecutors; Criminal procedure